Islamic Hospitals in the Indonesian Health Legal System from the Perspective of Maqāṣid Al-Sharī’ah - Darodjat, Rafan; Imamulhadi, Imamulhadi; Setiawati , Ria; Aisyah , Herini Siti; Eddyono, Luthfi Widagdo (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
As a country with a Muslim majority population, Indonesia has a need for faith-based health services, but there is a disparity between this need and the available institutional capacity. The national health system still faces challenges of structural inequality and accessibility barriers that hinder justice for vulnerable groups. The Islamic principle of Rahmatan lil 'Alamin (mercy for the universe) underlies that Sharia Hospitals are not exclusive institutions for Muslims, but rather a universal service model that brings benefits to all humanity without distinction of social status. This study uses empirical legal methods, analyzed with the theory of maqāṣid al-sharī’ah. Data were collected referring to document studies and field observations. The theory of maqāṣid al-sharī’ah is a principle in Islamic law that is used as an analytical framework in Islamic health governance. The results of the study provide concrete evidence that the development of health facilities based on the values ​​of justice and protection of life (hifz an-nafs) can strengthen the national health system. This study demonstrates the emergence of a service model that increases accessibility through the use of Sharia contracts such as ijarah and wakalah, as well as the transparent management of Islamic social funds (ZISWAF). The Islamic principle of Rahmatan lil 'Alamin underpins Sharia Hospitals, also as a universal service model that benefits all humanity regardless of social status. Therefore, this study confirms that Sharia Hospitals can function effectively as inclusive instruments in achieving equitable health standards by integrating religious ethical values ​​with the social goals of the state